معاشرتی اخلاقیات، اصلاح و تربیت: سیرتِ نبوی ﷺ کی روشنی میں ایک تحقیقی و تجزیاتی مطالعہ: Moral Values, Social Reform, and Character Building in the Light of the Prophetic Seerah - Dr. Tahira Firdous, (Al-Amīr Research Journal for Islamic Studies, 2025)
Human beings are inherently social by nature, and the formation of society is rooted in mutual interaction, cooperation, and shared moral values. While social coexistence fulfills material and emotional needs, the true stability and harmony of any society depend primarily on the moral character of its individuals. Moral values shape human behavior, regulate social relationships, and determine whether society becomes a source of peace and welfare or conflict and disorder. In this context, the Seerah of the Prophet Muhammad ﷺ presents a comprehensive and timeless framework for moral reform, social correction, and ethical training. The Prophet ﷺ not only preached moral values but practically demonstrated them in every sphere of life, transforming a morally fragmented society into an exemplary civilization based on justice, mercy, tolerance, and mutual respect. This study aims to explore the concept of morality (akhlaq), its philosophical and Islamic foundations, and its role in shaping individual and collective behavior. Special emphasis is placed on the Prophetic model of moral education and reform, highlighting how noble character contributes to social harmony, ethical balance, and sustainable societal development. The research argues that the revival of Prophetic ethics is indispensable for addressing contemporary moral crises and for building a peaceful, balanced, and morally conscious society. Keywords: Prophetic Seerah, Social Ethics, Moral Reform, Character Building, Islamic Society